2014
DOI: 10.1080/09205063.2014.921754
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of pseudozwitterionic polymer brushes with a systematic well-defined charge-bias control

Abstract: In this study, a pseudozwitterionic surface bearing positively and negatively mixed charged moieties was developed as a potential hemocompatible material for biomedical applications. In this work, hemocompatility of pseudozwitterionic surface prepared from copolymerization of negatively charged 3-sulfopropyl methacrylate (SA) and positively charged [2-(methacryloyloxy)ethyl] trimethylammonium (TMA) was delineated. Mixed charge distribution in the prepared poly(TMA-co-SA)-grafted surface can be controlled by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…The increasing content of −N­(CH 3 ) 3 + in mixed-charged SAMs can change the hydrophilic surface (water CA of about 20° in ratio 1:1 of oppositely charged components) into a hydrophobic surface (a completely positive charged component of −N­(CH 3 ) 3 + ) with over 60° CA for a water droplet in air . This conclusion supports the result that an outer −N­(CH 3 ) 3 + group in a long chain weakens the hydrophilicity of SAMs to some extent.…”
Section: Results and Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The increasing content of −N­(CH 3 ) 3 + in mixed-charged SAMs can change the hydrophilic surface (water CA of about 20° in ratio 1:1 of oppositely charged components) into a hydrophobic surface (a completely positive charged component of −N­(CH 3 ) 3 + ) with over 60° CA for a water droplet in air . This conclusion supports the result that an outer −N­(CH 3 ) 3 + group in a long chain weakens the hydrophilicity of SAMs to some extent.…”
Section: Results and Discussionsupporting
confidence: 79%
“…On the basis of the interactions and conformational change of mixed-charged monomers, it is not difficult to explain the reason for distinguishing underwater OCAs (DCE droplet) on different SAMs. The hydration strength of the −COO – group and the interchain interaction effect on hydration were taken into consideration in the following section, for the hydrophilic characteristic of the pseudozwitterion mainly appearing on the negatively charged monomer affirmed in a previous experimental work . The distance between two charged groups in a polymer chain can have effects on their inter- and intramolecular interactions, which can promote or inhibit the hydration of the charged groups; this experimental conclusion could also be understood at the molecular level from our work.…”
Section: Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Besides, with grafting mode (a), a few hydrophilic SO 3 groups stand out the SAMs to serve as hydrophilic topology, ameliorating the overall underwater oleophobicity to some extent. Jhong et al 70 prepared mixedcharged polymer brushes consisting of sulfonate and quaternary ammonium ions and found that the hydrophilicity of the polymer became stronger with an increasing content of polysulfonate. In their opinion, the cationic quaternary ammonium groups were surrounded by three methyl groups, causing it to have some degree of hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%